2017
DOI: 10.1097/md.0000000000008232
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional myocardial deformation in coronary vasospasm-related Takotsubo cardiomyopathy

Abstract: Rationale:Although transient reduction in the left ventricular ejection fraction is characteristic of Takotsubo cardiomyopathy, little is known about the time-course changes of myocardial deformation in coronary vasospasm-related Takotsubo cardiomyopathy.Patient concerns:We retrospectively analyzed the time-course changes in left ventricle, right ventricle, and left atrium strain values in a patient with coronary vasospasm-related Takotsubo cardiomyopathy. We found that not only left ventricular strain but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…One of the most established and unifying hypothesis pertains to sympathetic nervous system derangement and subsequent catecholaminergic imbalances 6, 7. The possible overlap between TTS and coronary vasospasm has been highlighted in the contemporary literature, although the specific nature of a possible relationship still warrants further ascertainment 1, 2, 8, 9, 10. As described in this case report, and in accordance with the current guidelines, the presence of both these entities can have therapeutic importance 1, 11.…”
supporting
confidence: 65%
“…One of the most established and unifying hypothesis pertains to sympathetic nervous system derangement and subsequent catecholaminergic imbalances 6, 7. The possible overlap between TTS and coronary vasospasm has been highlighted in the contemporary literature, although the specific nature of a possible relationship still warrants further ascertainment 1, 2, 8, 9, 10. As described in this case report, and in accordance with the current guidelines, the presence of both these entities can have therapeutic importance 1, 11.…”
supporting
confidence: 65%
“…In 2017, Hung et al . [ 166 ], performing an echocardiographic study in a patient with TS, found indirect signs of global coronary artery vasospasm in the form of a decrease in the deformation characteristics of the left heart chambers.…”
Section: Pathogenesis Of Stress Cardiomyopathymentioning
confidence: 99%